(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The present work focuses on establishing an actual manufacturing strategy that is suitable for the viable production of a substrate support for a palladium membrane; one that will lower production costs and be utilised to gain a competitive edge within the industry. Porous stainless steel supports for palladium membranes were produced using various types of stainless steel powders and methods. Observations indicate that SS powder 410L type Chengdu Huarui with particle sizes 1-5 μm, sintered in the HPT induction furnace at temperatures between 930- 950°C for a period of 8 minutes, in the presence of argon flow and vacuum, creates a first-class Pd membrane substrate. Notwithstanding that this result is the most economical method. The results of the study were based on the: roughness test, first bubble point test, and scanning electron microscope (SEM). The Chengdu Huarui powder type 410 L – 1-5 μm, which achieved the best results, produced a roughness test result of Ra 0.614 μm, and a bubble point pore size is 1.992 μm.